Soil and water conservation method adoption in a highly erosive watershed: the case of Southwest Oklahoma's Fort Cobb watershed. Issue 10 (24th August 2018) - Boyer, Tracy A.; Tong, Benjamin; Sanders, Larry D.
Abstract : A major source of pollution in agricultural landscapes is surface runoff and non-point source pollution generated from agricultural production practices. In-stream, stream bank and riparian conservation/management practices can be implemented to reduce sediment loading solely or in conjunction with upland practices. Survey results from producers in the Fort Cobb Reservoir watershed, a highly erosive watershed in southwest Oklahoma with a history of state and federal conservation programs, provide information required for improving understanding of operators' likelihood of adoption. Two models of soil and water conservation were estimated, a logit model of likelihood of enrollment and a Poisson model of the total number of practices adopted. Results reinforced previous findings that attitudes, gender and education influence conservation program enrollment. Farming experience, gender and attitudes towards conservation increased the total number of practices adopted.